EFFICACY OF KSHARASOOTRA LIGATION IN ARSHACHIKITSA W.S.R. TO THIRD DEGREE HAEMORRHOIDS (AYUSHDHARA, 2020)
Enumeration of the vast number of aetiological factors (including dietetic ingredients, habits of prolonged sitting during defaecation etc.) and the systematic description of pathogenesis are indicative of scientific knowledge of the disease haemorrhoid. Its incidence has increased due to Mithyaahara- Vihara (faulty food habits and improper sedentary lifestyle). In third degree haemorrhoid pile masses prolapses during defaecation and need to be replaced manually. Ksharasootra ligation is mentioned in treatment of Arshachikitsa. In present study efficacy of Ksharasootra ligation in Arshachikitsa w.s.r. to third degree haemorrhoids Ksharasootra has been prepared using the methodology based on the description in the Ayurvedic text of 17th centaury Rasakamadhenu with some necessary modifications.Ksharasootra Ligation was done in randomly selected 15 patients of either sex with third degree haemorrhoids. The study design was open, randomized, and prospective. The duration of the trial was of 15 days, with a follow-up of 4 weeks. The total effect of therapy was assessed based on Clinical & Postoperative criteria. Statistical analysis has determined significance of the treatment. For all values significance level was p